Engineering Characteristics and Reinforcement Approaches of Organic Sandy Soil - Jun Hu; Liang Jia; Wei Wang; Hong Wei; Juan Du (Advances in Civil Engineering)
Organic sandy soil is widely distributed throughout Hainan Island. This study aimed at addressing the distribution, composition, and formation of organic sandy soil. The engineering properties of organic sandy soil were examined. The experimental results showed that the coefficient of uniformity and coefficient of curvature were 2.07 and 1.25, respectively. The maximum dry density and optimum water content were 1.723 g/cm3 and 12.23%, respectively. The undrained shear strength of organic sandy soil was around 37.5 kPa. The effective stress parameters c and φ were around 4 kPa and 23°, respectively. The compound tangent-exponential model was adopted for capturing the stress-strain behavior of organic sandy soil. As the unconfined compressive strength of the cement-admixed organic sandy soil was much lower than that of ordinary sand, some innovative ground improvement technologies were proposed for stabilizing organic sandy soil, such as thermal pile, fiber, and steel-, bamboo-, and freezing-cemented soil columns. The main purpose of these technologies is to enhance the bearing capacity of organic sandy soil but reduce the usage of cement, as the latter is not an eco-friendly material.